In the CJEU Judges Trust: A New Approach in the Judicial Construction of Europe*. (10th October 2016) - Mayoral, Juan A.
Abstract: This article aims to highlight the relevance of judicial trust in international courts, focusing on national judges' trust in the Court of Justice of the European Union (CJEU). EU scholars have put a great deal of effort into explaining how legal and political factors affect the use of preliminary references by national courts. However, there is still a gap in the literature on the development of trust as a functional principle encouraging co‐operation between national and international courts. This article explores the nature, causes and potentials of judicial trust for the EU judicial system. A theory is offered in the article, which links national judges' trust in the CJEU to their corporatist identification and profile, to their attitudes towards the EU, and to their beliefs about the CJEU's ability to provide decisions that: 1) offer a clear guidance on European Union law, and 2) will not undermine Member States' legal order.